Religious ambiguity and religious diversity - McKim, Robert (Oxford ; New York : Oxford University Press, 2001)
"A central thesis of the book is that beliefs about religious matters ought to be held tentatively, with an awareness that the beliefs in question may be wrong. This applies to the beliefs of theists, of atheists, and of members of non-theistic religions alike. McKim shows the validity of this thesis by appealing to the theistic problem of the "hiddenness" of God; that is, the question of why, if God exists, it is not clear to everyone that this is so and why in general the facts about God are not clear to everyone."--BOOK JACKET.
1. The Hiddenness of God: Introduction -- 2. God's Hiddenness and the Possibility of Moral Action -- 3. God's Hiddenness, Freedom to Believe, and Attitude Problems -- 4. Trust and Other Goods of Mystery -- 5. The Hiddenness of God and Arguments for Atheism -- 6. The Hiddenness of God: Implications -- 7. Religious Diversity: Introduction -- 8. The Critical Stance I: Tentative Religious Belief -- 9. The Critical Stance II: Arguments and Objections -- 10. Religious Experience and Religious Belief -- 11. Alston on Religious Experience.
Includes bibliographical references (p. 255-273) and index.
Keywords: Religion -- Philosophy; Hidden God; Religious pluralism; Belief and doubt